Studi Pengaruh Kebijakan Bantuan Sosial Tunai Nasional terhadap Daya Beli di Kota Surabaya - Naysilla Chairani; Nisrina Zasmin; Rahman Raisuli; Akhmad Rasyid Rosidi; Ahmad Setiawan Nuraya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to evaluate the effectiveness of the National Cash Social Assistance (BST) policy on the purchasing power of communities in Surabaya. BST is a social protection program launched by the Indonesian government in response to the economic impact of the COVID-19 pandemic. The policy targets low-income and vulnerable groups through direct cash transfers, with the goal of maintaining basic consumption levels and preventing a sharp decline in household welfare. This research examines the extent to which the BST program has achieved its objectives, particularly in enhancing or sustaining the purchasing power of its beneficiaries in urban settings. The study employs an evaluative approach using a mixed-methods design, combining quantitative survey data with qualitative interviews involving aid recipients and local-level implementers. The findings indicate that the BST program had a positive short-term impact on household purchasing power, particularly in meeting essential needs such as food and utility expenses. However, several implementation challenges were also identified, including issues of inaccurate beneficiary targeting, delays in distribution, and the relatively small amount of assistance compared to actual household need. These results highlight that the effectiveness of social policy is not solely dependent on budget allocation but also on the precision of its implementation on the ground. Consequently, the study recommends improvements in beneficiary data updating, enhanced transparency in aid distribution, and the development of more adaptive program designs that reflect local socio-economic conditions. The findings are expected to serve as a valuable reference for policymakers in designing more efficient and sustainable social assistance programs in the future.